Education, Vocational Training and Research and Development: Towards New Forms of Labour Market Regulation - Chagas Lopes, Margarida (Journal of Research in Educational Sciences, 2011)
Labor market regulation and its relations with education and training have been performing an historical trajectory which closely intertwined with developments in economic thought. Under the form of human capital theories, neo-classical economics set the bridge between labor market equilibrium and education outputs for decades. The functionalist approach behind that lasting relationship was to be challenged by economic crises and globalization, which imposed the unquestionable supremacy of the demand for skilled work. Likewise, even if only that more strict perspective of education would prevail, which fortunately is not the case, time and hazard came to undertake its denigration on the grounds of a severe loss of regulatory efficiency as globalization was setting up. In this paper, we shed light on the increasing role which innovation is called to perform in labor market hetero regulation in the present phase of globalization. Depending on the institutional design throughout which R&D become embedded in nowadays societies, evidence clearly reveals how innovation strategies are to be found so asymmetrically implemented between developed and developing countries, thereby leading to the enlarging divide between the “new North” and “new South” globalization off springs.